The concept of self in the work of the innate sculptor Monem Furat (Journal of the College of Basic Education, 2022)
The current research focused on studying the sculptural works of the innate sculptor Moneim FuratB (The concept of subjectivity in the works of the innate sculptor Moneim Furat).The research included three chapters: the first of which was devoted to the methodological framework, and included the research problem, which can be summarized by asking about the reason that prompted the natural sculptor, Monem Furat, to make forms, some of which do not belong to the objective, tangible world, as if they were from a mysterious world, a world that has no way of access.